Politicizing self-advocacy: Disabled students navigating ableist expectations in postsecondary education - Emunah Woolf; Alise de Bie (Disability Studies Quarterly, 2022)
The student self-advocacy literature commonly claims that although self-advocacy is a vital skill that disabled students require to succeed in postsecondary education, many of these students experience a significant ‘skills-deficit’ in this area. This paper seeks to intervene in this literature by proposing opportunities to ‘politicize’ self-advocacy and move away from its individual, deficit-focused approach. To do so, the paper reports findings from a qualitative study at a research-intensive Canadian university. Interviews with 11 disabled students revealed a perception that there is an institutionally endorsed ‘right way’ to self-advocate that included expectations to: (1) register for formal accommodations; (2) embody visible/physical disability; (3) perform less disabled; and (4) make others comfortable. Rooted in ableism, these harmful expectations adopt misconceptions of disability as predictable and visible, and burden students with demands that they make their self-advocacy convenient for those to whom they are self-advocating. As a form of resistance to these ableist expectations, students described their own ‘better way’ of negotiating self-advocacy and disability on campus. This ‘better way’ offers opportunities for ‘politicizing’ self-advocacy by recognizing ableism and the harms of the self-advocacy model, affirming disabled student knowledge and community, and enacting their visions for institutional change. Vital to this politicization is a move away from staff and nondisabled-led initiatives like self-advocacy training to address a perceived skills-deficit in individual students. Politicizing self-advocacy moves instead towards disabled students as full partners in conducting research and informing student services and staff training based on their collective lived expertise and strategic practices.